Bless Her Heart!: Does Apparent Concern Help Women in Reputational Competition? - Reynolds, Tania A. (Tania Arline) (author)
A Dissertation submitted to the Department of Psychology in partial fulfillment of the requirements for the degree of Doctor of Philosophy. === Spring Semester 2018. === February 12, 2018. === Female competition, Gossip, Intrasexual competition, Morality, Prosociality, Self-deception === Includes bibliographical references. === Roy F. Baumeister, Professor Co-Directing Dissertation; Jon K. Maner, Professor Co-Directing Dissertation; Laura Arpan, University Representative; Andrea Meltzer, Committee Member; Paul Conway, Committee Member; Jesse Cougle, Committee Member.